Pengembangan Aplikasi E-Crm pada PT Trafoindo Prima Perkasa - Honni, Honni; Herman, Robertus Tang; Iswanto, Kurniawan (CommIT (Communication and Information Technology) Journal, 2008)
Various surveys show that the key to corporate success lies not only on the product or service being offered but how far the company’s efforts to satisfy the needs of its customers. Companies have to provide products or services that match customer needs and wants, and then maintain close relations with customers. Customer loyalty will be the key to success, not only in the short term but sustainable competitive advantage. This is because customer loyalty has strategic value for the company. One way that proved effective and successful to meet and satisfy customer needs is through the CRM (Customer Relationship Management). CRM is not new in the business world. Customer Relationship has long been applied by traditional businessmen. Technology in the form of a web can be utilized as a catalyst in improving the quality of CRM. Combining Technology and CRM in a business called E-CRM. E-CRM application development web based on PT Trafoindo Prima Perkasa aims to analyze and design company and customer needs. The research method used in this writing is descriptive survey method primarily associated with the customer. The analysis tool used is the model porter five forces and industry analysis: CPM Matrix, the External Factor Evaluation Matrix (EFE), the Internal Factor Evaluation Matrix (IFE), SWOT Matrix, IE Matrix, SPACE Matrix, and Grand Strategy Matrix to identify alternative strategies can be applied. Alternative strategy is then measured with a Matrix QSP charm, coupled with the approach of Object Oriented Analysis and Design as the basis for the development of E-CRM application based on web. Conclusions obtained are E-CRM applications have produced work as expected.Keywords: development, application of E-CRM, Trafoindo Prima Perkasa